Penerapan Model PBL Berbasis CRT untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar - Ngaini, Dwi Nur; Fadlillah, M.; Matwani, Matwani (Lembaga Yasin AlSys, 2025)
This study is motivated by the low learning outcomes of fifth-grade students in the IPAS subject, particularly in Chapter 7 with the theme